Obstacles to the Implementation of Death Penalty Sanctions for Perpetrators of Corruption in Indonesia - Ali Masyhar; Cahya Wulandari; Avilla Deva Aryanda (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The implementation of the death penalty remains controversial, especially when viewed through the lens of human rights such as the right to life and freedom from torture. In Indonesia, the death penalty is enforced for serious crimes, but not yet applied to corruption. This research explores the possibility of applying the death penalty to corruption cases and identifies the obstacles hindering its enforcement. Using a normative legal research approach, this study examines both primary and secondary legal materials. Corrupt acts in Indonesia are punishable by imprisonment, restitution, and in severe cases, the death penalty. The enforcement of penalties is part of Indonesia's criminal justice system, encompassing legal substance, legal structure, and legal culture. From a criminal policy perspective, the death penalty may serve as a deterrent and contribute to social welfare. However, its implementation faces challenges, including weak legal foundations, concerns over human rights, and pressure from international human rights agreements.